Cover Feature: Tetraacylstannanes as Long‐Wavelength Visible‐Light Photoinitiators with Intriguing Low Toxicity (Chem. Eur. J. 33/2018). Issue 33 (6th June 2018) - Radebner, Judith; Eibel, Anna; Leypold, Mario; Jungwirth, Nina; Pickl, Thomas; Torvisco, Ana; Fischer, Roland; Fischer, Urs Karl; Moszner, Norbert; Gescheidt, Georg; Stueger, Harald; Haas, Michael
Abstract : A new photoinitiating system based on tin as the central atom was synthesized for the first time. The photoreactivity of this compound class was investigated and shown to be excellent for applications with long‐wavelength irradiation. Tetraacylstannanes break the limiting border of 450 nm and can therefore be cured with light sources emitting beyond that barrier. Intriguingly, a low toxicity for the compounds was found, which paves the way for the implementation of tetraacylstannanes in biomedical applications. More information can be found in the Communication by J. Radebner and M. Haas et al. onpage 8281 .